Auto parts market in the context of legalization of parallel imports - A. V. Salnikova; A. V. Molotkov (Вестник университета)
The article assesses the share of counterfeit products on the Russian domestic market highlighting the most counterfeited product categories. On the basis of the analysis of key indicators of the automotive parts market, preconditions for the presence of large volumes of counterfeit products in the segment have been identified. Correlation of parallel imports and the counterfeit auto parts number increase has been established. The paper presents recommendations for combating the importation of counterfeit products in the context of parallel imports. The most significant of them are the extension of digital labeling to a wide category of automotive components, establishment of domestic production of spare parts and components, stimulation of Russian manufacturers by providing targeted loans and tax incentives.